Baisc life support education in secondary schools : the effects of multicenter controlled trial of bls outreach program on knowledge & perception toward resuscitation among the secondary school teachers & children - Nik Idsamuddin, Nik Ab Rahman (Pusat Pengajian Sains Perubatan, 2013)
Out-of-hospital cardiac arrest (OHCA) is a major public health problem. It affects all communities worldwide. One of the most common causes of cardiac arrest is acute myocardial infarction. However, recognition of cardiac arrest is not always straightforward especially for laypersons. Therefore, the survival rates among OHCA victim still remain low. Early bystander CPR is one of the most important factors to improve rate of survival among OHCA. We targeted the school teachers & children because they are quick learners, easy to motivate and also competent to provide effective chest compression. The aim of this study was to determine the effectiveness of CPR training on knowledge and attitude among secondary school children in Kota Bharu, Kelantan. This study also serves as a starting point to create a database that other centres in the nation will be able to add on to. This is a prospective interventional study. It was conducted from January 2012 until June 2012. The validated questionnaire was designed based on AHA Guidelines 2010. Six secondary schools in Kota Bharu, Kelantan were chosen to be part of this study. Three schools were selected as a control group and remaining three as an intervention group. The study subjects were obtained from one class of Form 2, 3 and 4 based on simple randomization for both study groups. The intervention group was given a lecture, video show, pamphlet and practical session on CPR training. Meanwhile, the control group was given a booklet on hazard of smoking to overcome learning effect. The questionnaires were distributed pre-intervention and two weeks post-intervention for both study groups and collected on the same day by the researcher. Statistical analysis was used using software SPSS version 18.0.1. A total of 967 secondary school teachers & children were analyzed. It comprised of 372 respondents in the control group and 336 respondents in the intervention group. Majority of the study subjects were Malays. No significant difference in the distribution of study subjects according to form (p=0.356) and school category (p=0.086). Majority of the study subjects in the control 73.9% (167) and intervention groups 64.5% (162) had no CPR training prior to this study. Only 26.1% (59) from control group and 35.5% (89) from intervention group had been trained on CPR. The mean (SD) total knowledge scores for overall respondents was 62.43 (13.68) in the intervention group and 62.29 (12.11) in the control group out of possible maximum score of 100. For total attitude scores, the mean (SD) was 19.33 (4.51) in the intervention group and 17.85 (4.52) in the control group out of possible maximum score of 28. The mean differences of knowledge and attitude scores between both study groups were 8.31 (p<0.001) and 2.39 (p<0.001) respectively regardless oftime.The respondents on both study groups had more than average level of knowledge scores and good positive attitudes on resuscitation at baseline level. Following CPR training program, it has proven to improve their level of knowledge and attitudes significantly as compared to those who were never been trained. Since majority of the students have no CPR training, our results suggest that teachers & children of all school should be provided with CPR training. The subject should be included in the school curriculum.